Industrial water pollution control - Eckenfelder, W. Wesley (William Wesley), 1926- (Boston : McGraw-Hill, 2000)
Source and characteristics of industrial wastewaters; Wastewater treatment processes; Pre- and primary treatment; Coagulation, precipitation, and metals removal; Aeration and mass transfer; Principles of aerobic biological oxidation; Biological wastewater treatment processes; Adsorption; Ion exchange; Chemical oxidation; Sludge handling and disposal; Miscellaneous treatment processes.
Includes bibliographical references and index.
Keywords: Sewage; Purification; Sewage -- Purification; Factory and trade waste -- Purification